3.46 μm Q-switched Er3+:ZBLAN fiber laser based on a semiconductor saturable absorber mirror. (September 2021) - Fang, Zhiqiang; Zhang, Chunxiang; Liu, Jun; Chen, Yu; Fan, Dianyuan
Highlights: Highly efficient 3.5 μm Er:ZBLAN fiber laser. Passively Q-switched fiber laser. Mid-infrared pulsed fluoride fiber laser. Q-switching using semiconductor saturable absorber mirror. Abstract: By adopting a InAs based semiconductor saturable absorber mirror (SESAM), we have demonstrated a 3.46 μm passively Q-switched Er 3+ :ZBLAN fiber laser. An amplified spontaneous emission (ASE) seeded 1973 nm pump source is introduced to enhance the temporal stability. Stable 3.46 μm Q-switched pulse trains are obtained with a maximum repetition rate of 58.71 kHz and corresponding pulse width of 2.47 μs. The maximum average output power and single pulse energy are 63 mW and 1.4 μJ, respectively. The pulse characteristics with respect to the two pump powers are also evaluated. The results prove that the commercial SESAMs in stock have the capacity to extend the operation wavelength to the mid-infrared (mid-IR) wavelength region beyond 3.0 μm.